MOTIVASI GURU BAHASA INGGRIS DALAM MEMILIH KARIER MENGAJAR: STUDI KASUS DI SEKOLAH MENENGAH ATAS AIRMADIDI - SIBY, YANET RIBKA; MARENTEK, ANDRIYANI; MANUS, JEANE A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThe research is entitled ?Motivasi Guru Bahasa Inggris dalam Memilih Karier Mengajar: Studi Kasus di Sekolah Menengah Atas Airmadidi?. The objectives of this research are to identify and classify the English Teachers? types of motivation in choosing teaching as a career. And also, it is to analyze and describe the main motivations that exist in English Teachers?. This research uses a descriptive method. The writer collected the data by interviewing English Teachers with a total of 7 participants from two schools, SMA N I Airmadidi and SMK Klabat Airmadidi. The writer has found 3 types of motivation from the results of this study namely Altruistic Motives, Intrinsic Motives and Extrinsic Motives. The findings of this research showed that 4 English Teachers chose Altruistic Motives, 2 English Teachers? chose Extrinsic Motives and 1 English Teachers? chose Intrinsic Motives. In this research, the writer also found 3 main motivations specifically that appear most often. First, factors from family and parents count 10 times. Second, educate count 7 times. The third, to build or shape of children character counted 4 times and the main motivation in general are extrinsic motives totaling 16, altruistic motives totaling 13 and followed by intrinsic motives totaling 5.      Keywords:  Motivation, English Teachers?, Career